2017
DOI: 10.1080/09537287.2017.1302102
|View full text |Cite
|
Sign up to set email alerts
|

On the integration of due date setting and order release control

Abstract: This paper calls for a paradigm shift in the production control literature away from assuming due date setting and order release are two independent decision levels. When order release is controlled, jobs do not enter the shop floor directly but are retained in a pre-shop pool and released to meet certain performance targets. This makes the setting of accurate planned release dates -the point at which jobs transition from the pool to the shop floor -a key consideration when setting due dates. We develop a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…As in previous simulation studies on Workload Control (e.g. Land and Gaalman 1998;Fredendall et al 2010;Thürer et al 2012Thürer et al , 2017Fernandes et al 2017), it is assumed that all materials are available, and all necessary information regarding shop floor routings, processing times, etc. is known.…”
Section: Workload Control Order Release and Time Limit Policiesmentioning
confidence: 99%
“…As in previous simulation studies on Workload Control (e.g. Land and Gaalman 1998;Fredendall et al 2010;Thürer et al 2012Thürer et al , 2017Fernandes et al 2017), it is assumed that all materials are available, and all necessary information regarding shop floor routings, processing times, etc. is known.…”
Section: Workload Control Order Release and Time Limit Policiesmentioning
confidence: 99%
“…They concluded that the system's performance is improved for mean tardiness and SDL. Thürer et al 18) integrated due date setting rules and ORR considering SIDST using simulation. They considered two ORR policies, i.e., periodic and LUMSCOR with PRT sequencing rule.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the early implementations of WL was Bertrand's workload concept presented in Land and Gaalman (1996). It has received much attention in the literature, with researchers testing different methodologies to account for job workload (Oosterman et al 2000), investigating the integration of due-date information (Thürer et al 2017), and trying to integrate O/C (Thürer et al 2016a, b). In all cases, the most commonly implemented version is as follows:…”
Section: Wlworker+mentioning
confidence: 99%